Rancang Bangun Aplikasi Penilaian Kinerja Pegawai Yayasan Pusdiklat PAL Indonesia Surabaya Menggunakan Spiral Model - Hari Aspriyono (JTIS: Journal of Technopreneurship and Information System, 2019)
Employee performance assesment is an important activity in an institution to measure the merits of it’s employee performance. Yayasan Pusdiklat PAL Indonesia is an institution that always assesses the performance of its employees in a certain period with the aim of evaluating, appreciating and motivating the performance of its employees. The employee performance assessment process carried out by Yayasan Pusdiklat PAL Indonesia is assessed by his superiors and also by other employees. The research method used in developing application of employee performance assesment at Yayasan Pusdiklat PAL Indonesia is spiral model. In the spiral model, the application development does not conducted directly in full of the needs of the application being developed, but the application will be developed in stages using a prototype. Employee performance assessment applications that are built using the Codeigniter Framework and spiral model are able to produce applications that run well, because it goes through several stages of testing and improvement. The more testing, especially by involving the user, Yayasan Pusdiklat PAL Indonesia and the improvements made will result in a better system or application.Keyword : spiral model, Employee performance appraisal applications, codeigniter, framework